Physiological and biomechanical analyses of a 200 m all-out front crawl - Marcos Franken; Kelly de Jesus; Vitória Miranda; Karla de Jesus (Acta Scientiarum. Health Sciences, 2024)
This study aimed to analyze the effort effects of laps on general stroke kinematics and associate the peak oxygen uptake (V̇O2peak) with all-out 200-m front crawl time. Fourteen regional-level swimmers (age 16.14 ± 2.68 years; height 1.65 ± 0.08 m; body mass 58.17 ± 7.76 kg) performed an all-out 200 m front crawl. Oxygen consumption (V̇O2) was measured post-all-out 200 m trial to assess physiological variables and stroke mechanics was assessed based on the time to perform 10 m and time to perform three complete arm stroke cycles. The 1st lap had a higher stroke rate (SR) than the 3rd lap (44.73 vs. 40.82 cycles⋅min-1; p = 0.04). The 1st lap showed a higher mean swimming speed (SS) than the following laps (1.45 ± 0.10 vs. 1.35 ± 0.11 vs. 1.30 ± 0.11 vs. 1.28 ± 0.13 m⋅s-1; p < 0.01) and the 2nd was greater than the 4th lap (p < 0.05). The swimming index (SI) was smaller and greater in the 3rd lap compared to the 1st and 4th laps (2.60 ± 0.65 vs. 2.97 ± 0.71 vs. 2.43 ± 0.50 m2⋅s-1⋅cycles-1), respectively. There was moderate and inverse coefficient of correlation between the V̇O2peak and 200-m time (rho = -0.653; p < 0.05). Our findings suggest that V̇O2peak values should be assessed in post 200-m all-out effort due to the strong shared variance with performance and a pacing strategy should be adopted during the race to avoid detrimental effects of fatigue.